2022
DOI: 10.3846/cs.2022.14307
|View full text |Cite
|
Sign up to set email alerts
|

Arts and Culture as Creative Learning of Students Through Cultural Product Design

Abstract: The study explores whether a design activity could promote creative learning expression and development among students regarding arts and culture issues through cultural product design. Therefore, students engage in designing a cultural product model. The study aims to analyze their ability to develop arts and culture through sketches and an appearance model. The research project was conducted to observe students (aged 18–20 years) as they negotiated and shared creative ideas during the process of cultural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Similarly, the acceptance of creative solutions in food industry, including food novelties, varies among societies and individuals (Yeniyurt & Townsend, 2003). Younger generations are often considered more open to innovations due to their exposure to rapid changes and technological advancements (Packalen & Bhattacharya, 2019;Boonpracha, 2022), but there are exceptions to this generalization, as observed in the obtained results. Various factors such as education, socio-economic background, cultural upbringing, and personal beliefs influence individuals' openness to innovations (Sparke & Menrad, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, the acceptance of creative solutions in food industry, including food novelties, varies among societies and individuals (Yeniyurt & Townsend, 2003). Younger generations are often considered more open to innovations due to their exposure to rapid changes and technological advancements (Packalen & Bhattacharya, 2019;Boonpracha, 2022), but there are exceptions to this generalization, as observed in the obtained results. Various factors such as education, socio-economic background, cultural upbringing, and personal beliefs influence individuals' openness to innovations (Sparke & Menrad, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…Tradition and lifestyle are design pillars. 794 on a particular meaning, story, emotions, and other abstract symbols, as well as other projects that may constitute a crucial element of the design theme of cultural goods as a component of the transition [23]. This current research and development project creates new corporate identities that are shown through the traits of mascots (characters) that can be used to make a wide range of other products.…”
Section: Resultsmentioning
confidence: 99%
“…Designcommunication enables and supports the development of soft skills (Boonpracha, 2022), provides a highly flexible framework and a sound methodological background that goes beyond the familiar, known and habitual toolkit of the past to offer a new vision to its users (Park & Lee, 2021). The methodology is a deliberate combination of design and business communication disciplines.…”
Section: Communication Integrated Into Developmentmentioning
confidence: 99%